2013
DOI: 10.1002/cb.1404
|View full text |Cite
|
Sign up to set email alerts
|

Materialism and charitable giving: Can they co‐exist?

Abstract: It is generally believed that Western societies are more materialistic compared with other cultures. However, it has also been observed that Americans are among the most generous of all, contributing their time, money, and effort to charitable causes. This research attempted to examine the relationship between materialism and charitable giving. Results of an empirical study suggest that it is possible for materialism to co-exist with charitable giving. Implications of the findings and suggestions for future re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
8

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 42 publications
3
31
0
8
Order By: Relevance
“…There was no support for the propositions that there are two separate segments of the population (one primarily materialistic and the other primarily altruistic), or that these conflicting values reflected the country's state of economic development (i.e., that more advanced countries can focus more on higher-order, less-materialistic needs) (Mathur 2013). Mathur (2013) noted, however, that the positive relationship between materialism and charitable giving could be attributed to either common antecedents (e.g., a desire for status) or to the possibility that the motivations for materialistic behavior and charitable behavior coincide. We suggest a materialistic person may be generous due to egoistic type motivations rather than agapic, self-sacrifice, or more altruistic motivations.…”
Section: Relationship Between Materialism and Charitable Behaviorsmentioning
confidence: 72%
See 4 more Smart Citations
“…There was no support for the propositions that there are two separate segments of the population (one primarily materialistic and the other primarily altruistic), or that these conflicting values reflected the country's state of economic development (i.e., that more advanced countries can focus more on higher-order, less-materialistic needs) (Mathur 2013). Mathur (2013) noted, however, that the positive relationship between materialism and charitable giving could be attributed to either common antecedents (e.g., a desire for status) or to the possibility that the motivations for materialistic behavior and charitable behavior coincide. We suggest a materialistic person may be generous due to egoistic type motivations rather than agapic, self-sacrifice, or more altruistic motivations.…”
Section: Relationship Between Materialism and Charitable Behaviorsmentioning
confidence: 72%
“…As noted earlier though Mathur (2013) examined the relationship between materialism and generosity and found that there can be a positive relationship between these two apparently conflicting values. This suggests that the two values can co-exist in the same person at the same time, but may alternate as the dominant value over time.…”
Section: Relationship Between Materialism and Charitable Behaviorsmentioning
confidence: 90%
See 3 more Smart Citations